융의 원형과 집단무의식이 중년의 위기 극복에 미치는 역할에 관한 기초 연구 - 배나래; 임진섭; Na-Rae Bae; Jin-Seop Lim (미래기술융합논문지, 2024)
This study is a theoretically based study that understands the midlife crisis from the perspective of Jung's Archetypes and the Collective Unconscious, explores psychological changes, and suggests methods that can be applied to social welfare practice. The midlife crisis is not simply a period of confusion, but is viewed as an important journey toward individualization and self-actualization. We seek to understand how Jung's archetypes appear in middle age and what meaning they have for the psychological changes that occur during adulthood. In addition, it explains the impact of the collective unconscious on an individual's experience and behavior during a midlife crisis, and provides theoretical basic research to social welfare practitioners and researchers studying midlife to help clients overcome the midlife crisis more positively. I want to do it. The purpose is to suggest that the integrated approach of Jungian psychology in social welfare practice and education can play a role as meaningful theoretical basic research in effectively supporting the midlife crisis 이 연구는 중년 위기를 융의 원형(Archetypes)과 집단무의식(Collective Unconscious) 관점에서 이해하고, 심리적 변화를 탐색하며 사회복지실천에 적용할 수 있는 방법을 제시하는 이론적 기초 연구이다. 중년의 위기는 단순한 혼란의 시기가 아닌, 개별화(Individuation)와 자기실현(Self-Actualization)을 향한 중요한 여정으로 간주한다. 융의 원형이 중년기에 어떻게 나타나며, 중년기 시기에 발생하는 심리적 변화에 어떤 의미를 가지는지를 이해하고자 한다. 또한, 집단무의식이 중년의 위기 동안 개인의 경험과 행동에 미치는 영향을 설명하며, 사회복지실천가나 중년을 연구하는 연구자들에게 내담자의 중년 위기를 보다 긍정적으로 극복할 수 있도록 돕는 이론적 기초연구를 제공하고자 한다. 사회복지실천 및 교육에 있어 융 심리학의 통합적 접근이 중년의 위기를 효과적으로 지원하는 데 의미있는 이론적 기초연구의 역할을 할 수 있음을 시사한다는 데 목적이 있다.